KETIDAKJUJURAN AKADEMIK PADA SAAT UNBK TAHUN 2017 - Herdian Herdian (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2018)
INTRODUCTION The use of komputer in the national exam is a new breakthrough in the national examination sistem in Indonesia. The use of komputers is expected to minimize the practice of dishonesty in National Examination work that had sounded